Improving An Early Children's Discipline Through Hypnoparenting Methods - Trianasari, Dessy; Sunaryo, Ilham (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
Hypnoparenting is knowledge about educating and caring for children by controlling children's actions and emotions through a series of hypnotic suggestion activities. Objective: To examine the literature, journal, and documents of research findings that identify hypnoparenting methods for improving child discipline early on. Method: Search for research journals using certain words in the 2016-2020 period. There ware 105 research journals on child discipline and hypnoparenting methods both nationally and internationally, 46 journals meet the criteria, 59 journals did not meet the criteria, only 20 journals were selected to meet the criteria. 15 national journals and 5 international journals. Results and discussion: The reviewed literature shows that it significantly increases children's discipline early on. Statistical analysis proves that this method can increase the knowledge and actions of parents, teachers, and the community in caring for and educating children from an early age. Conclusion: Hypnoparenting method can make it easier for parents, teachers, and community to significantly improve children's discipline from an early age with positive suggestions that have been applied.